Learning from the Past, Teaching for the Future: A Forum - Horowitz, Sara R.; Veprinska, Anna (Canadian Jewish Studies / Études juives canadiennes, 2024)
The Mark and Gail Appel Program in Holocaust and Antiracism Education: “Learning from the Past, Teaching for the Future” (TFTF) is a tri-national program that brings students from Canada, Germany, and Poland to sites of Holocaust memory to focus on the history, experience, representation, and memorialization of the Holocaust and its implications for other instances of atrocity, racism, and genocide. This forum gathers five voices from the 2013-2014 cohort of TFTF in order to reflect, a decade after the program, on the program’s challenges, opportunities, and lasting impacts. The forum documents the various ways TFTF has influenced the lives and career trajectories of each of the forum participants. The forum is bookended by reflections from its editors—a program organizer and a program participant—on the potentials of experiential learning, the promise of an international network of educators, and the processing that a program like TFTF continues to demand.